Paraneoplastic Dermatomyositis Associated with Metastatic Seminoma - Hidekazu Yoshie; Ryuto Nakazawa; Wataru Usuba; Hiroya Kudo; Yuichi Sato; Hideo Sasaki; Tatsuya Chikaraishi (Case Reports in Urology)
We report the first case in Japan of paraneoplastic dermatomyositis with pure seminoma, a tumor that extremely rarely accompanies dermatomyositis. The patient presented to the hospital with muscle weakness and erythema and was diagnosed with dermatomyositis from skin biopsy. Routine radiological screening revealed testicular tumor and massive lymph node metastases. We initially performed orchiectomy along with conventional immunotherapy. However, muscle weakness gradually worsened, and he eventually showed dysphagia and forced respiration and became bedridden. Although he seemed close to being too unstable to tolerate further treatment, we started carefully adjusted chemotherapy comprising 4 courses of etoposide plus cisplatin, which proved highly successful. Lymph node metastases completely disappeared and swallowing and respiration fully normalized after completing chemotherapy. We believe that this clinical success was due to our decision to initiate chemotherapy even in such a weak patient.